To be different, or to be the same? It’s a question (and theory) of strategic balance - Deephouse, David L. (Strategic Management Journal, 1999)
This paper addresses the performance consequences of firm-level strategic similarity. Past research observed that firms face pressures to be different and to be the same. By differentiating, firms reduce competition. By conforming, firms demonstrate their legitimacy. Both reduced competition and legitimacy improve performance. This paper begins building a theory of strategic balance by synthesizing the differentiation and conformity perspectives. The theory directs attention to intermediate levels of strategic similarity where firms balance the pressures of competition and legitimation. Empirical support for the theory is found in a longitudinal study of commercial banks. Several suggestions for developing a theory of strategic balance conclude the paper. The theory’s major implication is that firms should be as different as legitimately possible. Copyright © 1999 John Wiley & Sons, Ltd.